Comparative Highly Efficient Production of β-glucan by Lasiodiplodia theobromae CCT 3966 and Its Multiscale Characterization - Jesús J. Ascencio (Fermentation, 2021)
Lasiodiplodan, a (1→6)-β-d-glucan, is an exopolysaccharide with high commercial value and many applications in food, pharmaceuticals, and cosmetics. Current industrial production of β-glucans from crops is mostly by chemical routes generating hazardous and toxic waste. Therefore, alternative sustainable and eco-friendly pathways are highly desirable. Here, we have studied the lasiodiplodan production from sugarcane bagasse (SCB), a major lignocellulosic agricultural residue, by Lasiodiplodia theobromae CCT 3966. Lasiodiplodan accumulated on SCB hydrolysate (carbon source) supplemented with soybean bran or rice bran (nitrogen source) was 16.2 [6.8 × 103 Da] and 22.0 [7.6 × 103 Da] g/L, respectively. Lasiodiplodan showed high purity, low solubility, pseudoplastic behavior and was composed of glucose units. Moreover, the exopolysaccharides were substantially amorphous with moderate thermal stability and similar degradation temperatures. To our knowledge, this is the first report on the highest production of SCB-based lasiodiplodan to date. L. theobromae, as a microbial cell factory, demonstrated the commercial potential for the sustainable production of lasiodiplodan from renewable biomass feedstock.